Cooking breakfast after a brain injury - Tanguay, Annick N.; Davidson, Patrick S. R.; Guerrero Nuñez, Karla V.; Ferland, Mark B. (Frontiers in Behavioral Neuroscience, 2014)
Acquired brain injury (ABI) often compromises the ability to carry out instrumental activities of daily living such as cooking. ABI patients’ difficulties with executive functions and memory result in less independent and efficient meal preparation. Accurately assessing safety and proficiency in cooking is essential for successful community reintegration following ABI, but in vivo assessment of cooking by clinicians is time-consuming, costly, and difficult to standardize. Accordingly, we examined the usefulness of a computerized meal preparation task (the Breakfast Task; Craik & Bialystok, 2006) as an indicator of real life meal preparation skills. Twenty-two ABI patients and 22 age-matched controls completed the Breakfast Task and the Rehabilitation Activities of Daily Living Survey (RADLS; Salmon, 2003). Patients also prepared actual meals, and were rated by members of the clinical team. As expected, the ABI patients had significant difficulty on all aspects of the Breakfast Task (failing to have all their foods ready at the same time, over- and under-cooking foods, setting fewer places at the table, and so on) relative to controls. Surprisingly, however, patients’ Breakfast Task performance was not correlated with their in vivo meal preparation. These results indicate caution when endeavoring to replace traditional evaluation methods with computerized tasks for the sake of expediency.